Burdens of idiopathic developmental intellectual disability attributable to lead exposure from 1990 to 2021 and projection to 2035 in China: findings from the 2021 global burden of disease study - Song, Chaoqun; Deng, Feidan; Qiao, Lichun; Lin, Minghao; Zhang, Hui; Li, Miaoqian; Zhao, Changwei (Frontiers in Public Health, 2025)
ObjectiveTo analyze the burden and trend of idiopathic developmental intellectual disability (IDII) attributed to lead (Pb) exposure in China from 1990 to 2021 and to predict the trend from 2022 to 2035.MethodWe used the Global Burden of Disease Study (GBD) 2021 data to estimate disability-adjusted life years (DALYs) and age-standardized DALY rate (ASDR) of IDII attributable to Pb exposure. The annual average percentage change (AAPCs) was estimated to evaluate the changing trend of IDII ASDR attributable to Pb exposure from 1990 to 2021. The age-period-cohort (APC) and Bayesian age-period-cohort (BAPC) was used to assess and predict changes in the DALYs of IDII attributable to Pb exposure.ResultFrom 1990 to 2021, the number of DALYs and rate of the total population, males and females in China showed a fluctuating and decreasing trend. The APC showed that the age deviation had an upward trend and then decreased, the period deviation showed an ‘N’ shaped trend, and the cohort deviation model showed a trend of first increasing and then decreasing. The BAPC model predicts that the number of DALYs and ASDR will continue to decline, with males declining faster than females, and that by 2035, females will have higher DALYs and ASDR than males.ConclusionFrom 1990 to 2035, the burden of IDII attributed to Pb exposure in China showed a downward trend. But the DALYs and ASDR in females will be higher than that in males in 2035. It is essential to prioritize intervention, prevention, and control measures for females.